2014
DOI: 10.1111/trf.12612
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hematopoietic progenitor cell donor characteristics predicting successful mobilization: results of an Italian multicenter study

Abstract: In healthy donors it is possible to predict successful HPC mobilization by donor sex, age, WBC count, and G-CSF form and dose. Furthermore, based on these data, it may be possible, at least in parental setting, to modulate G-CSF dosage on the basis of donor characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
28
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 28 publications
8
28
2
Order By: Relevance
“…Vasu and colleagues reported a reduced post–G‐CSF CD34+ cell count in females in their analysis of 639 allogeneic donors. Others found the same correlation …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Vasu and colleagues reported a reduced post–G‐CSF CD34+ cell count in females in their analysis of 639 allogeneic donors. Others found the same correlation …”
Section: Discussionsupporting
confidence: 58%
“…Different variables from the blood count and clinical chemistry have been associated with the mobilization efficacy in former publications . In particular, a higher baseline PLT count was associated with increased CD34+ levels in the peripheral blood immediately before apheresis .…”
Section: Discussionmentioning
confidence: 99%
“…Published studies showed that preapheresis CD341 cell count in PB is the best predictor of CD341 cells in the apheresis products 13,16 and for the estimation of the number of procedures needed to reach the target dose. 17 In this series, we confirmed the most frequent shortterm adverse events described in other studies. 14,15 The incidence of bone pain was higher in the ODD cohort, but predominantly minor and transient and, in any case, no donor had to stop treatment.…”
Section: Discussionsupporting
confidence: 93%
“…12,[23][24][25][26][27][28] In this small cohort, the strongest predictors of higher CD34 cell mobilization were younger age, higher baseline platelet count, higher baseline circulating CD34, and higher AUC of plerixafor. Other factors associated with CD34 mobilization were CXCL12 change from baseline to 30 minutes, male gender, and a lower graft content of pDCs.…”
Section: Discussionmentioning
confidence: 99%